ST-segment elevation myocardial infarction: are women being discriminated?. (14th October 2021) - Oliveira, C C; Vilela, F; Flores, R; Medeiros, P; Pires, C; Mane, F; Braga, C; Marques, J; Costa, J
Abstract: Background: Although outcomes in patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary interventions (PCI) have improved, a gender disparity exists, with women showing higher mortality. Objectives: To assess gender differences in presentation, management and in-hospital, at 30-days, 6-months and 1-year after STEMI mortality. Methods: We collected data from 809 consecutive patients treated with primary PCI and compared the females versus males. Results: Women were older than man (69, 1±14, 6 vs. 58, 5±12, 7 years; p<0.001) with higher prevalence of age over 75 years (36.7% vs. 11.7%; p<0.001), diabetes (30, 6% vs. 18, 5%; p=0.001), hypertension (60.5% vs. 45.9%; p=0.001), chronic kidney disease (3.4% vs. 0.6%; p=0.010) and acute ischemic stroke (6.8% vs. 3.0%; p=0.021). At presentation, women had more atypical symptoms, less chest pain (90.3% vs. 95.6%; p=0.014) and greater clinical severity (cardiogenic shock (10.7% vs. 5.4%; p=0.011). There were no differences in the symptom-first medical contact me (95.0 min vs. 80.5 min; p=0.215); however, women had longer time until reperfusion (264.0 min vs. 212.5 min; p=0.001) and were less likely to receive optimal medical therapy (aspirin-93.1% vs. 99.2%; p<0.001; P2Y12 inhibitors 91.9% vs. 98.2%; p<0.001; beta-blockers-90.8% vs. 95.1%; p=0.032; ACEIs- 88.1% vs. 94.8%; p=0.003). In-hospital mortality (9.6% vs. 3.5%; p=0.001), at 30-days (11.3% vs. 4.0%; p<0.001), 6-months (14.1% vs. 4.7%; p<0.001) and 1-year (16.4% vs. 6.3%; p<0.001) was significantly higher in women. The multivariate analysis identified age over 75 years (HR=4.25; 95% CI [1.67–10.77]; p=0.002), Killip class II (HR=8.80; 95% CI [2.72–28.41]; p<0.001), III (HR=5.88; 95% CI [0.99–34.80]; p=0.051) and IV (HR=9.60; 95% CI [1.86–48.59]; p=0.007), acute kidney injury (HR=2.47; 95% CI [1.00–6.13]; p=0.051) and days of hospitalization (HR=1.04; 95% CI [1.01–1.08]; p=0.030) but not female gender (HR=0.83; 95% CI [0.33–2.10]; p=0.690) as independent prognostic factors of mortality. Conclusions: Compared to men, women with STEMI undergoing primary PCI have higher mortality rates. Our results suggest that this is not due to the gender itself, but due to the women worse risk profile, the higher reperfusion time related with system delays and the minor probability of receiving the recommended therapy. Efforts should be made to reduce these gender differences. FUNDunding Acknowledgement: Type of funding sources: None.